2004
DOI: 10.1111/j.1525-1497.2004.30384.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered communication

Abstract: OBJECTIVE:To investigate patient preferences for a patientcentered or a biomedical communication style. DESIGN: Randomized study.SETTING: Urgent care and ambulatory medicine clinics in an academic medical center. PARTICIPANTS:We recruited 250 English-speaking adult patients, excluding patients whose medical illnesses prevented evaluation of the study intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(87 citation statements)
references
References 72 publications
10
73
3
1
Order By: Relevance
“…11 Historically, a number of initiatives have aimed to equalise power within the HCP-patient relationship, to encourage the adoption of a partnership approach and to enhance the sharing of decisions about care; 13,28 but patients have continued to report a lack of PCC. 12 More recent studies have demonstrated that training HCPs can enhance a PCC approach, especially interventions that focus on consultation style.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Historically, a number of initiatives have aimed to equalise power within the HCP-patient relationship, to encourage the adoption of a partnership approach and to enhance the sharing of decisions about care; 13,28 but patients have continued to report a lack of PCC. 12 More recent studies have demonstrated that training HCPs can enhance a PCC approach, especially interventions that focus on consultation style.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Health care professionals are also shown to benefit from a PCC approach to care with reports of enhanced personal empowerment and increased job satisfaction. 10,11 Despite such benefits, research suggests that practitioners' continue to fail to elicit patient main concerns during consultations and many patients remain reluctant to disclose key factors relating to their condition and / or care. 2,[9][10][11] Thorne 12 highlights that health care professionals (HCP) and patient communication is a pivotal opportunity within the consultation, with effective dialogue having the potential to optimise autonomy and maintain independence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female doctors have longer consultations (roter et al 1991;van Dulmen and Bensing 2000), are more patient-centred (Bertakis and azari 2012), show more partnership and empathy (roter et al 2002) and have a stronger psychosocial orientation (roter and hall 2004). These are all types of communication which are highly appreciated by most patients (Swenson et al 2004). however, a recent meta-analysis of studies reporting patients' satisfaction with male and female doctors also found a statistically significant -but very small and barely clinically relevant -gender difference in patient satisfaction (hall et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although patient-centered care is often favored, precautions are still necessary. This paradigm requires a patient's willingness to participate in a specific manner, which can be seen as a challenge that may induce increased stress and anxiety in patients who already feel overwhelmed by their situation (e.g., Step et al, 2009;Swenson et al, 2004).…”
Section: Self-advocacymentioning
confidence: 99%